2013
DOI: 10.1021/ol401815n
|View full text |Cite
|
Sign up to set email alerts
|

Hypervalent Iodine Catalyzed Generation of Nitrile Oxides from Oximes and their Cycloaddition with Alkenes or Alkynes

Abstract: Hypervalent iodine catalyzed oxidation of aldoximes using oxone as a terminal oxidant generates nitrile oxides, which react with alkenes and alkynes to give the corresponding isoxazolines and isoxazoles in moderate to good yields. This reaction involves active hypervalent iodine species formed in situ from catalytic iodoarene and oxone in the presence of hexafluoroisopropanol in aqueous methanol solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(73 citation statements)
references
References 75 publications
1
69
0
Order By: Relevance
“…Therefore, there is a clear necessity for metal-free protocols. This green approach has been conducted by different oxidative reagents such as oxone, [43][44] iodine, [45][46][47] iodobenzene trifluoroacetate, 48 iodobenzene diacetate, [49][50][51] tert-butyl hypoiodite 52 or chloramine-T. 53 However, these new protocols have several inconveniencies such as stability, price and manipulation of reagents. The importance of the used solvent has been recently addressed by the use of aqueous biphasic protocols, [54][55] ionic liquid, 56 and aqueous polyethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is a clear necessity for metal-free protocols. This green approach has been conducted by different oxidative reagents such as oxone, [43][44] iodine, [45][46][47] iodobenzene trifluoroacetate, 48 iodobenzene diacetate, [49][50][51] tert-butyl hypoiodite 52 or chloramine-T. 53 However, these new protocols have several inconveniencies such as stability, price and manipulation of reagents. The importance of the used solvent has been recently addressed by the use of aqueous biphasic protocols, [54][55] ionic liquid, 56 and aqueous polyethylene glycol.…”
Section: Introductionmentioning
confidence: 99%
“…These procedures utilize catalytic hypervalent iodine species 15 generated in situ from iodoarenes 16 and appropriate terminal oxidants such as m-CPBA or Oxone (Scheme 3). 32,33 The reaction mechanism of the catalytic synthesis of oxadiazoles 10 has been investigated by NMR spectroscopy and ESImass spectrometry (Section 4).…”
Section: Page 101mentioning
confidence: 99%
“…3,6,[84][85][86] Recently the first examples of iodine(III) catalyzed oxidative cycloaddition reactions of aldoximes have been reported. [32][33][34]64,87,88 In 2013, our group was the first to report the hypervalent iodineinduced catalytic cyclization of aldoximes. 32 We have found that oxidative heterocyclization of various aldoximes 65 with alkenes 66 or alkynes 67 in the presence of catalytic aryl iodide and Oxone as the oxidant affords the corresponding isoxazolines 68 or isoxazoles 69 in moderate to good yields (Scheme 20).…”
Section: Oxidative Cyclization Of Aldoximes Using Catalytic Hypervalementioning
confidence: 99%
See 1 more Smart Citation
“…[1] Among the known procedures for the oxidative cyclization of aldoximes with alkenes or alkynes, particularly important are the procedures utilizing stoichiometric amounts of organohypervalent iodine(III) reagents, [2][3][4][5][6][7] such as (diacetoxyiodo)benzene, [3] iodosylbenzene, [4] [hydroxy(tosyloxy)]iodobenzene, [5] and [bis(trifluoroacetoxy)iodo]benzene. [6] Previously, our group has first found that catalytic hypervalent iodine(III) species, generated in situ from iodoarenes and Oxone, could promote the oxidative cyclization of aldoximes with alkenes or alkynes.…”
mentioning
confidence: 99%